Acute regrowth and dissemination of a mature spinal cord teratoma after partial resection. (1st September 2018) - Kawai, Momotaro; Nagoshi, Narihito; Iwanami, Akio; Mikami, Shuji; Tsuji, Osahiko; Fujita, Nobuyuki; Yagi, Mitsuru; Watanabe, Kota; Ishii, Ken; Nakamura, Masaya; Matsumoto, Morio
Abstract : A 23-year-old man presented with difficulty walking and leg pain and numbness. MRI revealed a cystic mass at Th11–12 and a pineal-region tumour. The patient underwent surgery to resect the thoracic-level mass. The tumour adhered strongly to the neural tissue and could only be partially resected. On pathological examination, the resected tumour was diagnosed as a mature teratoma. The tumour regrew and disseminated within 3 months after resection. Both the spinal cord tumour and the tumour in the pineal region shrank significantly after chemotherapy and radiotherapy. Although the tumour was pathologically diagnosed as a mature teratoma, we suspect that the residual tumour contained an immature or malignant component. Thus, careful follow-up observation is mandatory after partial resection of a mature teratoma. In addition, because teratomas can disseminate in the central nervous system, the presence of teratoma should prompt an examination of both the spinal cord and brain.